Peripheral Blood Inflammation Indicators as Predictive Factors for Treatment Response Assessed by MRI in Cervical Cancer Patients Referred for Radiotherapy - Chunyu Liang; Zhiyuan Xu; Guohui Yang; Jianxun Lv; Xinping Shen; Kusheng Wu (Clinical and Experimental Obstetrics & Gynecology)
Backgroud: Radiotherapy (RT) with or without concurrent chemotherapy is regarded as the standard therapy for locally advanced cervical cancer (International Federation of Gynecology and Obstetrics [FIGO] stage IB2 and above). However, markedly different responses to RT are seen among patients with similar FIGO stages.The study aimed to evaluate the peripheral blood inflammation indicators that may have predictive value for treatment response in cervical cancer patients referred for RT. Methods: This was a retrospective study that enrolled 75 patients who had stages IB2 to IVA cervical cancer, and who underwent RT alone or concurrent chemoradiation therapy (CCRT). All patients were treated at the department of Clinical Oncology of the University of Hong Kong-Shenzhen hospital between November 2015 and April 2020. The endpoint was treatment response assessed by magnetic resonance imaging (MRI) according to the Response EvaluationCriteria in Solid Tumors (RECIST). Multivariate logistic regression models were used to identify predicting values of peripheral blood inflammation indicators, including the systemic immune-inflammation index (SII), neutrophil/lymphocyte ratio (NLR), tumor-related leukocytosis (TRL), platelet/lymphocyte ratio (PLR) and monocyte/lymphocyte ratio (MLR). Results: The percentage of complete response (CR) was significantly different between different groups of peripheral blood inflammation indicators. The percentage of CR was 64.3%, 57.9%, 81.8% and 48.3% respectively in low SII, NLR, PLR and MLR groups, which was significantly higher than in the high SII group (34.0%), high NLR group (32.4%), high PLR group (30.2%) and high MLR group (35.3%). Multivariate logistic regression revealed that the TRL and PLR were significant prognostic factors for treatment response with an odds ratio of 0.18 (95% confidence interval [95% CI] 0.04–0.77) for TRL and 16.36 (95% CI 3.67–73.04) for PLR. Conclusions: The result revealed that a TRL-negative or lower PLR tumor was associated with radiosensitivity, which may provide important information for the prediction of treatment response in cervical cancer patients referred for RT.